Experiences of family medicine specialists in providing health care for lesbian, gay, bisexual and transgender patients: a qualitative study in East Coast Peninsular Malaysia - Mohd Amin, Siti Noorfadhilah; Muhamad, Rosediani; Draman, Samsul; Mohd Zulkifli, Maryam; Syed Jaapar, Sharifah Zubaidah (Kulliyyah of Medicine, International Islamic University Malaysia (IIUM), 2024)
INTRODUCTION: Lesbian, Gay, Bisexual and Transgender (LGBT) patients continue to report discrimination in healthcare setting despite the efforts of the primary healthcare offering community friendly services in Malaysia. This qualitative study aimed to provide understanding of this current issue and to explore the challenges that family medicine specialists (FMSs) from East Coast of Peninsular Malaysia face when dealing with LGBT patients. MATERIALS AND METHODS: 30 FMSs working in East Coast Peninsular Malaysia were interviewed through a phenomenological framework using semi-structured in-depth interviews of LGBT patients. The interviews were recorded in audio format, transcribed verbatim, and subjected to Braun and Clarke’s thematic analysis. We discerned common themes that can be elucidated through the lens of Leininger’s Theory of Culture Care (TCC) and the Sunrise Enabler Model (SEM). RESULTS: Three overlapping themes of the transcriptions were developed; (1) Multidimensional understanding of LGBT described how FMSs saw the LGBT community as diverging from societal norms, yet acknowledge their vulnerability as integral members of the society, (2) obstacles to providing culturally competent care stemmed from inadequate training, an unsupportive clinic environment, and the self-stigma experienced by patients, and (3) barriers to incorporating spiritual needs for holistic care arose in situations where there was insufficient spiritual health training or a preference to concentrate on physical and emotional well-being to uphold trust. CONCLUSION: The findings on this study reflect the need for proper training of healthcare personnel to deliver a holistic, culturally competent care for LGBT patients. A collaborative effort with relevant authorities is also needed to successfully overcome those challenges.